CP-078 Optimisation of biological therapy in established rheumatoid arthritis patients in real life clinical practice. (14th February 2016) - Cárdenas, M; Font, P; De la Fuente, S; Castro-Villegas, MC; Romero-Gómez, M; Ruiz-Vílchez, D; Escudero, A; Ortega-Castro, R; Calvo-Gutiérrez, J; Collantes-Estévez, E
Abstract : Background: Optimisation of biological therapy (BT) in patients with rheumatoid arthritis (RA) in remission is a strategy employed in rheumatology practice in recent years, consisting of dose reduction or enlargement of dose intervals. Some studies suggest that patients in sustained clinical remission (CR) could get the same benefit with a lower dose. Purpose: To assess the effectiveness and efficiency of optimisation strategy in patients with established RA in clinical remission treated with BT 1 year after. Material and methods: Observational prospective study of patients diagnosed with RA (ACR 1987–2010 criteria) in a tertiary referral hospital. From November 2013, patients with established AR and treated with BT, after reaching sustained clinical remission (DAS28 value <2.6), were optimised by enlargement of the dose interval and followed for 12 months. Decision taking involved a multidisciplinary team. Data examined included demographic data, clinical variables and use of direct healthcare resources. Enlargement interval depended on the clinical response. Regimens were: etanercept 50 mg/10–14 days, infliximab 3 mg/9–10 weeks, adalimumab 40 mg/21–30 days, golimumab 50 mg/5–6 weeks, tocilizumab 8 mg/kg/5–6 weeks, abatacept 750 mg/5–6 weeks. Statistical analysis was performed using IBM SPSS v.17.0 program. Multiple analysis was performed to identify confusion or prognosis factors for CR. Effectiveness was measured as the proportion of patients maintaining CR after 1 year of treatment (DAS28 value <2.6). Costs were assessed from the hospital perspective. Results: 70 patients were optimised, 81% were women, mean age 57 years, a DAS28 mean at baseline optimisation of 2.45 ± 0.94, mean time of CR before optimisation of 17.5 ± 16.5 months. 41 patients (58.5%) maintained optimisation therapy and CR after 1 year (DAS28 mean 2.31 ± 0.77). 18 patients (63%) had to return to a standard regimen and reached CR or low disease activity again after 1 year (DAS28 mean 2.88 ± 0.92). The effectiveness of BT used in the optimisation strategy was infliximab 7/10, etanercept 11/25, adalimumab 6/10, tocilizumab 10/13, abatacept 5/8, golimumab 2/3 and certolizumab 0/1. Optimisation saved 23.75% of the total direct health costs. Combining saved cost and effectiveness, the most efficient drug was adalimumab. Conclusion: Optimisation of BT can be a useful performance and efficiency strategy to manage patients with established RA who are in sustained CR. No conflict of interest.